Long-term variations in pH in coastal waters along the Korean Peninsula - Y.-W. Lee; M.-O. Park; S.-G. Kim; T.-H. Kim; Y. H. Oh; S. H. Lee; D. Joung; D. Joung (Biogeosciences)
Declining seawater pH, associated with rising atmospheric CO2 levels, adversely affects marine organisms and ecosystems, thereby posing a considerable risk to coastal fisheries and economies. However, the effects of long-term pH variations in coastal waters remain poorly understood. In this study, we investigated the variability in pH in the coastal waters of Korea over an 11-year period (2010–2020) and sought to identify the principal drivers of pH fluctuations. Unlike the persistent pH declines observed in the open oceans and other coastal systems, Korean coastal waters showed no persistent pH variation, thus indicating that local biogeochemical processes may have a greater influence than atmospheric CO2 in determining aquatic pH. Analysis of environmental data including temperature, salinity, chlorophyll a, and dissolved oxygen (DO) revealed a strong correlation between pH and DO. However, instances of pH changes exceeding those predicted by DO depletion alone indicate the influence of additional biogeochemical factors. As global seawaters warm, reduction in DO is anticipated to cause a further decline in the pH of coastal waters. This trend could have a pronounced influence on Korean coastal waters, which support extensive aquaculture operations integral to the local and national economies. Consequently, high-frequency monitoring is essential for extending the current time series and predicting future water quality.